Sources of valuable breeding traits and their use in creation of barley varieties adapted to conditions of Volga-Vyatka region - L. P. Kokina; L. M. Shchekleina; A. V. Kunilova (Аграрная наука Евро-Северо-Востока, 2017)
Usage of genetic variability is one of the factors of successful breeding of spring barley (Hordeum vulgare L.). Main factors that limits barley productivity in Volga-Vyatka region are duration of growing season and its particular phases, low natural fertility and increased acidity of soils, spring-summer drought, as well as multiple diseases. Four hundred and thirteen collection numbers of different ecological-geographic origins were studied. For breeding work the most interesting were early accessions: Stimul, Acha, Bagan (Russia), Surpriz and Adapt (Ukraine) and other. There are accessions combined productivity and earliness - Dina, Andrey, Belogorsky 90 (Russia), Syabra (Belarus), Druvis, Malva (Latvia), Veslets (Bulgaria), Danuta (German), City (France), and Codac (Canada). Varieties Bionik, Omsky golozerny 1 (Russia), Gonar (Belarus), Malva, Druvis (Latvia), 23007 (Dutch), and Azure (USA) are lodging resistant. Varieties which have complex of valuable breeding trait (productivity, number of productive stems, grain mass per ear and per plant, 1000 grain mass) are: Zavetny, Natali (Russia), Yakub (Belarus), Rodos, Korona Lashego (poland), Jdumeja, Druvis (Latvia), Fillippa, Nue grosse (Sweden), Hja (Finland), 23007 (Dutch), City (France), and other. Varieties Tandem, Chelyabinsky 96, Chelyabinsky 99, Sonet (Russia), Firlbeks Union (Switzerland), Lamba (Dutch), Canasta (Great Britain), Buck (Canada), Bonita (Argentina), and other are resistant to osmotic stress; varieties Dobry, Novichok, Khlynovsky, Vikont, Partner, Priazovsky 9, Zernogradets 770, Signal, Rus', Luka (Russia), Dzivosny (Belarusь), Dzherelo (Ukraine), and other - are resistant to aluminum-acid stress. Varieties Petr, Lel', Munach (Russia), Sultan (Netherlands) have resistance to loose smut in artificial infectious background; varieties Dina, Forward, Medicum 336, Musson (Russia), Edem, Surpriz, Mironovsky 86, Get'man (Ukraine), Margret, Xanadu, Orthega (German), Buck (Canada) and other have complex resistance to some fungi diseases. Combining of disease resistance and high number of productive stems, grain mass per ear and per plant, 1000 grain mass are characteristic for varieties Zevs, Zavetny, Natali (Russia) Ilek 34 (Kazakhstan), Codak (Canada) and other. Lines and varieties created with use of sources of valuable trait are studied in North-East Agricultural Research Institute in all stages of breeding process. Working collection consist of 114 covered and 17 naked accessions of spring barley is used successfully at creation of adaptive varieties.